The Impact of Social Media Marketing Activities on Value Equity, Brand Equity, and Relationship Equity in Ngarsopura Market of Surakarta - Sumaryanto, Sumaryanto; Widajanti, Erni; Susanti, Nani Irma (Westscience Press, 2024)
Even in Surakarta, traditional marketplaces continue to play an essential role in the commercial activities that take place in Indonesia. Because of the proliferation of digital technology, the utilization of social media in marketing endeavors has become increasingly important. On the other hand, there is currently a dearth of research about the influence that social media marketing operations have on value equity, brand equity, and customer relationship equity in traditional markets. In the Ngarsopuro Market in Surakarta, the purpose of this study is to provide an explanation of the potential social media marketing actions that have the potential to influence those three equity factors. The strategy known as Partial Least Square (PLS) is utilized as a device for doing data analysis in this study. Through the use of questionnaires, information was gathered from 230 individuals who have visited Ngarsopuro Market and have engaged in the practice of online shopping. A favorable impact on value equity, brand equity, and relationship equity has been observed at Ngarsopuro Market as a result of the utilization of social media, as demonstrated by the findings of the study. In addition, the investigation revealed that value equity, brand equity, and customer relationship equity all play a key role in the decision to make a purchase in the Ngarsopuro Market. Therefore, in order to maintain conventional markets, it is anticipated of sellers that they would make more efficient use of social media, give relevant information about their products, and increase consumer loyalty.